2002
DOI: 10.1034/j.1399-3038.2002.01056.x
|View full text |Cite
|
Sign up to set email alerts
|

A 500‐ml plastic bottle: An effective spacer for children with asthma

Abstract: Inhaled therapy using a metered-dose inhaler (MDI) with attached spacer has been increasingly recognized as the optimal method for delivering asthma medication for acute attacks and chronic prophylaxis. However, in developing countries the cost and availability of commercially produced spacers limit the use of MDI-spacer delivery systems. A 500-ml plastic bottle has been recently adapted to function as a spacer. This article reviews the current data on the efficacy of this bottle-spacer and discusses its advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 22 publications
1
19
1
Order By: Relevance
“…However, our results are inconsistent with previous studies that demonstrated superiority of a 500-mL plastic bottle in comparison with the MDI alone (17,18,20). The reason for this is unclear; however, the plastic bottles we used did not have the same shape as the one tested in previous studies (17,18,20). Although our bottles had rather short necks (see Fig.…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…However, our results are inconsistent with previous studies that demonstrated superiority of a 500-mL plastic bottle in comparison with the MDI alone (17,18,20). The reason for this is unclear; however, the plastic bottles we used did not have the same shape as the one tested in previous studies (17,18,20). Although our bottles had rather short necks (see Fig.…”
Section: Discussioncontrasting
confidence: 96%
“…Our results are also consistent with previous studies that have shown that adding a spacing device to an MDI reduces the oropharyngeal dose (30,31). However, our results are inconsistent with previous studies that demonstrated superiority of a 500-mL plastic bottle in comparison with the MDI alone (17,18,20). The reason for this is unclear; however, the plastic bottles we used did not have the same shape as the one tested in previous studies (17,18,20).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations